The defendant’s bad character in the wake of the Criminal Justice Act 2003 - Rao, A (2014)
This thesis examines the interpretation and application of the Criminal Justice Act 2003 (UK), Part 11 Chapter 1, which came into force on 15 December 2004. Part 11 Chapter 1 concerns evidence of bad character, a concept approximately comparable with common law similar fact evidence, in relation to all parties who may be connected with a criminal trial. The admission and use of similar fact evidence has often been the subject of controversy, and the significant changes made by the CJA 2003 have attracted their own body of support and criticism. The nine chapters of this thesis attempt an in-depth study into the impact of the legislation on the robustness and effectiveness of the criminal trial, and consider whether the criminal trial is suited to the level of exposure of bad character now facilitated by the CJA. In particular, the thesis focuses upon the key provisions governing the uses of bad character evidence of the defendant: the seven gateways set out in s 101 of the CJA. The operation of those gateways and their accompanying explanatory provisions is examined through a combination of engagement with the Law Commission’s Report 273 (which preceded the enactment of the legislation), the range of Court of Appeal cases dealing with the legislation, and academic commentary. It was foreshadowed by commentators and early case law that the new provisions might not be easy to interpret or apply, and subsequent cases have borne out this prediction. An analysis of the bad character provisions suggests that, even though the CJA was intended to provide clarity in regulation, it has itself led to confusion in some important respects. Certain central terms lack definition, and some provisions have unintended consequences. The case law reflects this in its frequent, often brief, and sometimes inconsistent analysis of the specific parts of the legislation, which can make it difficult to determine the defendant’s guilt or innocence in a precise and scrupulous manner.